2021
DOI: 10.1371/journal.pone.0260286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of SARS-CoV-2 seropositivity among people who inject drugs in the San Diego-Tijuana border region

Abstract: Background People who inject drugs may be at elevated SARS-CoV-2 risk due to their living conditions and/or exposures when seeking or using drugs. No study to date has reported upon risk factors for SARS-CoV-2 infection among people who inject drugs. Methods and findings Between October, 2020 and June, 2021, participants aged ≥18 years from San Diego, California, USA and Tijuana, Baja California, Mexico who injected drugs within the last month underwent interviews and testing for SARS-CoV-2 RNA and antibodie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 30 publications
4
59
3
Order By: Relevance
“… 25 A study conducted among people who inject drugs in Tijuana during the same period as this study found that 36.5% tested SARS-CoV-2 positive. 3 Our seroprevalence results are, therefore, consistent with the review by Hayward et al who concluded that migrants have been disproportionately affected during the pandemic, when compared with the native-born or general population and should be targeted in prevention efforts. 7 A report by the Organisation for Economic Co-operation and Development also concluded that immigrants are over-represented among COVID-19 cases in most countries, with the risk estimated to be twice that of native-born residents.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“… 25 A study conducted among people who inject drugs in Tijuana during the same period as this study found that 36.5% tested SARS-CoV-2 positive. 3 Our seroprevalence results are, therefore, consistent with the review by Hayward et al who concluded that migrants have been disproportionately affected during the pandemic, when compared with the native-born or general population and should be targeted in prevention efforts. 7 A report by the Organisation for Economic Co-operation and Development also concluded that immigrants are over-represented among COVID-19 cases in most countries, with the risk estimated to be twice that of native-born residents.…”
Section: Discussionsupporting
confidence: 91%
“…According to that study, the seroprevalence for the northwest region (including Baja California) was 40.7% 25. A study conducted among people who inject drugs in Tijuana during the same period as this study found that 36.5% tested SARS-CoV-2 positive 3. Our seroprevalence results are, therefore, consistent with the review by Hayward et al who concluded that migrants have been disproportionately affected during the pandemic, when compared with the native-born or general population and should be targeted in prevention efforts 7.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations